ECONOMIC VALUE ADDED, INVESTMENT OPPORTUNITY SET DAN KEBIJAKAN DIVIDEN - Mentari Ruth Caroline Zega; Alfonsa Dian Sumarna (Pusat P2M Politeknik Negeri Batam, 2025)
The pandemic has had a significant impact on the global capital market. The property and real estate sector is one of the sectors that has been dramatically affected by the pandemic. This is evident from the significant decline in stock trading volume in the property and real estate sector during the pandemic, compared to the previous year. This certainly attracts investors' attention to dividend policies and investment opportunities, considering several key factors, including Economic Value Added (EVA) and Investment Opportunity Set (IOS). This study aims to examine the economic added value, determine investment opportunities, and analyze dividend policies in the property and real estate sector on the Indonesian stock exchange during the 2019-2020 period. The sample determination employed a purposive sampling method, resulting in a sample of 52 companies. The analysis technique used is multiple linear regression, utilizing SPSS 25 as the statistical software. Based on the research analysis, it was found that, partially, the EVA and IOS variables had an effect, albeit not significant, on dividends, both partially and simultaneously.